Assessing critical success factors for ERP implementation satisfaction: a study of consultants participation and user training - Soltani, Sheida (2013)
An Enterprise resource planning (ERP) system is a company wide information system that integrates all aspects of a business and promises one database, one application across the entire enterprise. ERP implementation has been an important activity for improving efficiency and is a critical investment that can significantly affect future performance of a company. Consultant participation and user training are essential factors that can contribute to ERP implementation satisfaction. Studies examining the effects of consultant participation and user training on ERP implementation satisfaction are rare. Thus, this present study was designed to fill this gap in research. A relevant research model was developed to test three (3) hypothesized paths among the study’s variables, namely consultant participation, user training, ERP implementation satisfaction. Data was collected by survey questionnaires from 109 of ERP users. The Smart PLS tool was used for data analysis. In sum, the results of this research show that (1) ERP implementation satisfaction depends on consultant participation especially on the quality of consultants’ services and user training. (2) User training plays a mediator role between consultant participation and ERP implementation satisfaction.